Interior point control and observation for the wave equation - A. Y. Khapalov (Abstract and Applied Analysis)
This paper is concerned with the approximate and exact controllability properties of the wave equation with interior point controls entering via the concentrated force, the velocity of the displacement and the moment. The emphasis is given to the moving point controls and their dual observations whose advantages and disadvantages, versus the static ones, are analyzed with respect to the space dimension, the duration of the control time interval and the function spaces involved.